О запасе устойчивости по фазе в электродинамической виброиспытательной системе - Божко, А.Е. (Видавничий дім "Академперіодика" НАН України, 2008)
A method of definition of the stability margin in phase for the systems reproducing vibrations with electrodynamic vibrobenches is developed.